2019
DOI: 10.1016/j.cub.2019.10.057
|View full text |Cite
|
Sign up to set email alerts
|

The Early Ediacaran Caveasphaera Foreshadows the Evolutionary Origin of Animal-like Embryology

Abstract: The Ediacaran Weng'an Biota (Doushantuo Formation, 609 million years old) is a rich microfossil assemblage that preserves biological structure to a subcellular level of fidelity and encompasses a range of developmental stages [1]. However, the animal embryo interpretation of the main components of the biota has been the subject of controversy [2, 3]. Here we describe the development of Caveasphaera, which varies in morphology from lensoid, to a hollow spheroidal cage [4], to a solid spheroid [5], but has large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 51 publications
2
25
0
Order By: Relevance
“…It is true that there are no traces of crown-group metazoans in the Bitter Springs and Svanbergfjellet Formation biotas; but the same is surely also true of both the Lantian and the Weng'an biota. The latter in particular preserves a series of intriguing and much debated embryo-like balls of cells, but despite this demonstrating the possibility of crown group metazoans being preserved here [109], none have to date been found that have commanded anything close to universal assent [110]. Furthermore, although [108] regard the Lantian as providing the soft maximum for bilaterians, there is (also) surely no evidence for them in the Weng'an biota either (or, indeed, the Avalonian 'Ediacaran' assemblages).…”
Section: Discussionmentioning
confidence: 93%
“…It is true that there are no traces of crown-group metazoans in the Bitter Springs and Svanbergfjellet Formation biotas; but the same is surely also true of both the Lantian and the Weng'an biota. The latter in particular preserves a series of intriguing and much debated embryo-like balls of cells, but despite this demonstrating the possibility of crown group metazoans being preserved here [109], none have to date been found that have commanded anything close to universal assent [110]. Furthermore, although [108] regard the Lantian as providing the soft maximum for bilaterians, there is (also) surely no evidence for them in the Weng'an biota either (or, indeed, the Avalonian 'Ediacaran' assemblages).…”
Section: Discussionmentioning
confidence: 93%
“…Initially described as animal embryos (Xiao and Knoll, 2000), the affinities of these fossils have been linked to various protists, sulfur-oxidizing bacteria, volvocine green algae and embryonic, larval or adult animals (reviewed by Xiao et al, 2014;Cunningham et al, 2017b). One form, Caveasphaera, exhibits patterns of cellular development analogous to gastrulation in animals, and has been plausibly assigned a holozoan, but not necessarily metazoan, affinity (Yin et al, 2019) (Node 1, Fig. 1).…”
Section: Ediacaran Periodmentioning
confidence: 99%
“…In the history of interpretations of the Weng'an biota, Y-shaped cell interfaces are seen also in Megasphaera, where they have been commonly interpreted to indicate animal affinity (5,12,22); however, Y-shaped cell interfaces are encountered in embryo-like conformations of cells in diverse eukaryotes including ciliates, rhodophytes, and nonmetazoan holozoans (18). Yin et al (13) reviewed the diversity of embryo-like developmental stages that occur in eukaryotes. Among these, the known developmental stages of Helicoforamina bear a strong resemblance to the early binary reductive palintomic stages of rhodophyte embryos (23,24).…”
Section: The Holozoan Affinity Of Helicoforaminamentioning
confidence: 99%